LITERATURE REVIEW: MATERNAL ANXIETY AND PARTICIPATION IN INTEGRATED SERVICES POST DURING PANDEMIC COVID-19 - Farahita, Griseld Adiel; Hendrati , Lucia Yovita (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2023)
Background: The spread of the COVID-19 virus is a fairly big challenge and causes a lot of high anxiety in the community. Conditions from the pandemic also have an impact on various sectors, for example Integrated Services Post. Purpose: To analyze relationship between anxiety mothers and participation Integrated Services Post during pandemic COVID-19. Methods: This study was a literature review approach (literature review) by a narrative literature review which discusses the relationship between maternal anxiety and participation in the Integrated Services Post under five during the COVID-19 pandemic. The data source used secondary data in the form of journal-based articles obtained through the Google Scholar database. The inclusion criteria of this research were the year of publication in the range of 2020 to 2022, publication in Indonesian and English, and original research and full text. Results: All of the entire literature can prove that there was an association between maternal anxiety and participation in the Integrated Services Post under five during the COVID-19 pandemic. Maternal anxiety was caused by factors of community attitudes and the surrounding environment. Conclusion: The concern that occurs in mothers is caused by fear if the child or himself is exposed to Covid-19 during a visit to the Integrated Services Post, because even though they have implemented health protocols, the attitude of other visitors who do not comply with health protocols makes them feel unsafe.